Religious and Cultural Tourism in Sindh: A case study of Sufi Saints of Rural Sindh - Huma, Zil e (Annals of Human and Social Sciences, 2024)
This article explores the role of the Sufi Shrines in the religious and cultural tourism in Sindh Pakistan. In the religious and cultural life of rituals, saints, traditional beliefs, noises, trance, dance, and music in ethnic healing and spiritual illness/disease, shrines play a crucial role. In addition to being a center of Sufi devotion and religion, it is also a location where Muslims and non-Muslims engage in joyful activities. The spiritual and religious systems of Muslim social organizations, as well as its aesthetic and economic facets, are reflected in the architecture and design of sufi shrines, both locally and internationally. The methodological approach of this article is anthropological and based on the field work. Since visitors from all over the world have been visiting Sufi shrines since the Middle Ages, religious tourism has long been the standard in Sindh. The primary Sufi shrines that are the subject of this study piece are Lal Shabaz Qalandar and mystic poets Shah Abdul Latif Bhatai, Sachal Sar Mast.